Ontological Analysis of the Essence of Education: The Relationship between God, Man and Nature - Kusairi, Komarudin; sassi, Komarudin (Journal of English Language and Education, 2026)
This paper examines the essence of education from an ontological perspective by analyzing the fundamental relationship between God, human beings, and nature. Using an ontological-philosophical approach and library research, this study draws on classical and contemporary literature in philosophy of education, metaphysics, and epistemology. The analysis shows that education is not merely a process of knowledge transmission, but a humanizing and transcendental endeavor that integrates divine values, human potential, and the natural order. Ontology-based education positions humans as rational and spiritual beings with ethical and ecological responsibility as part of divine purpose. The study concludes that education should be reformulated toward an integrative and holistic paradigm that unites spiritual, intellectual, and ecological dimensions.